ACCESS CONTROL MODEL FOR DATA STORED ON CLOUD COMPUTING - Muhammad Talha Tahir Bajwa; Zartasha Kiran; Tehreem Fatima; Rameez Akbar Talani; Waseema Batool (Spectrum of Engineering Sciences, 2025)
Cloud computing can be referred as technology based on internet, having shared, adaptable foundation that can be utilized as administration by clients. Compositely cloud computing is software and hardware being conveyed by internet as a service. It is an extraordinary advancement innovation getting well known because of minimal effort, adaptability and versatility according to client’s necessity. The objectives of this research were to concentrate on client’s data security in cloud computing i.e. data storage security issues and how to limit unapproved access to information by proposing access control model. Accessible arrangements were introduced by the researcher and then an access control model was recommended. Many access model were accessible yet those model do not satisfy the security necessities as per service providers and cloud is always under assaults of hackers and data integrity, accessibility and protection were traded off. This research presented a model keeping in view the requirements of service providers that upgraded the information security in terms of integrity, accessibility and protection. The proposed model helped the hesitant clients to effectively choose to move on cloud while understanding the dangers related with cloud computing.